Zamia paucifoliolata, a new species of Zamia (Zamiaceae, Cycadales) from Valle del Cauca, Colombia - Calonje, Michael; López-Gallego, Cristina; Castro, Jonatan (Phytotaxa, 2018)
Zamia paucifoliolata, a new cycad species from the Pacific lowlands of Valle del Cauca, Colombia, is described and illustrated. It is distinguished from other species of Zamia by having an underground stem typically bearing large solitary leaves with eighteen or fewer leaflets, villous strobilar axes, microsporangia borne on both the abaxial and adaxial side of microsporophylls, and seeds that are longer than 18 mm. It is compared to Z. pyrophylla, Z. cunaria, and Z. ipetiensis, species which it most closely resembles.